The rare antlion genus Thaumatoleon Esben-Petersen, 1921 (Neuroptera: Myrmeleontidae: Nemoleontinae) newly recorded from mainland China, with first male description - Zheng, Yuchen; Liu, Xingyue (Zootaxa, 2021)
Thaumatoleon Esben-Petersen, 1921 is a monotypic antlion genus represented by T. splendidus Esben-Petersen, 1921 from the Oriental region. Previously, this genus was documented by only three female specimens. Here we report this genus from mainland China for the first time based on a male and two female specimens newly collected in Yunnan Province. A detailed re-description and distribution map of the genus are provided. A brief discussion on the relationships of Thaumatoleon within Nemoleontinae is also provided.